A new technique and software to optimize compression and data retrieval in the Material Examined section of taxonomic publications - Aguiar, Alexandre P.; Broad, Gavin R. (European Journal of Taxonomy, 2022)
Elusive flaws are identified in techniques widely adopted to organize the Material Examined sections in taxonomic publications, mostly regarding the usage of the term ibidem and the nesting of information such as country and states. Logical errors are identified that prevent objective retrieval of the original information and can hinder or block its interpretation, even in case-by-case analyses. It is demonstrated that the free usage of ibidem in the sense of “same as previous except as follows” compromises the interpretation of data, characterizing bad practice. Solutions are proposed for the precise usage of both the term ibidem and the nesting technique. A new technique for organizing, compressing, and presenting information, called grid-setting, is described and evaluated. Its most notable practical effect is that the Material Examined section becomes literally a coded data sheet, which can be accurately converted back to spreadsheet format. In addition, the grid-setting technique was able to generate texts up to 30% shorter than those edited with the best-known traditional techniques. The new ideas and fixes are incorporated into a new software, flexible enough to process varied and unlimited data into largely user-defined texts, which remain nevertheless universal in their format and logical interpretation.